2014
DOI: 10.4103/0255-0857.124296
|View full text |Cite|
|
Sign up to set email alerts
|

Nasal carriage of Methicillin-resistant Staphylococcus aureus among healthy population of Kashmir, India

Abstract: High prevalence of MRSA is a cause of concern and strategies to interrupt transmission should be implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
2
16
0
1
Order By: Relevance
“…In a study from Kashmir, India, community prevalence of 27.92% was noted with highest nasal carriage rate of 15.17% in the age group 30–39 years. Methicillin resistance was noted in 1.83% of the isolates . We found a higher MRSA prevalence, possibly due to the contact with health care environment by dialysis patients and uremia.…”
Section: Discussionmentioning
confidence: 63%
“…In a study from Kashmir, India, community prevalence of 27.92% was noted with highest nasal carriage rate of 15.17% in the age group 30–39 years. Methicillin resistance was noted in 1.83% of the isolates . We found a higher MRSA prevalence, possibly due to the contact with health care environment by dialysis patients and uremia.…”
Section: Discussionmentioning
confidence: 63%
“…An empiric broad spectrum antibiotic therapy with meropenem and azithromycin was administered instead of amoxicillin/clavulanic acid and clarithromycin previously given in the ED. On day 2, reconsidering the patient´s recent travel history and potential exposure to CA-MRSA [1], linezolid was added. On day 3, azithromycin was stopped and teicoplanin was started due to positive blood cultures for methicillin-resistant, Panton-Valentine leucocidin producing Staphylococcus aureus (PVL + MRSA).…”
Section: Casementioning
confidence: 99%
“…MRSA strains are a versatile and most significant nosocomial pathogen, often causing postsurgical wound infections almost exclusively of hospital origin described in 1961 [6]. MRSA infections account for 20-80% of all nosocomial S. aureus infectionsin many centers across the world [7,8] that lead to increased mortality, morbidity hospital stay, and costs [9,10]. WHO (2018) have reported that 64% of MRSA infected patients are more likely to die than non MRSA infected patients [11].…”
mentioning
confidence: 99%